Foreign women - women in foreign lands studies on foreignness and gender in the Hebrew Bible and the Ancient Near East in the first millennium BCE - Berlejung, Angelika 1961-; Grohmann, Marianne 1969- (Tübingen Mohr Siebeck, 2019)
The volume presents a collection of papers read during three workshops held in Leipzig (2016), Jerusalem (2017), and Vienna (2018). International scholars from different disciplines and methodological approaches explored gender-specific constructions of foreignness/strangeness in the Old Testament, Egypt, and Mesopotamia from their particular perspectives. They showed that when combined, strangeness/foreignness and gender can take on very different forms. Various processes of the "othering" of women are of importance, which differ from the "othering" of men. The contributions investigate specific questions, individual female figures and individual phenomena as model cases. The basic question was when, where, how and for what purpose the categories of foreignness and gender were connected and activated in literary tradition. The collection is a preliminary and basic work for further study of gender-specific concepts of foreignness/strangeness in the ancient Mediterranean cultures of the first millennium BCE. --
"This volume present a collection of papers read during three workshops held in Leipzig (2016), Jerusalem (2017), and Vienna (2018)" (Klappentext)
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Women in the Bible; Noncitizens -- Biblical teaching; Femmes dans la Bible; Women in the Bible; Women in the Bible; Aliens - Biblical teaching; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès; Konferenzschrift -- 2016 -- Leipzig; Konferenzschrift -- 2017 -- Jerusalem; Konferenzschrift -- 2018 -- Wien; Aufsatzsammlung